Sámi Cultural Heritage in Audiovisual Archives – Ethical Reflections on the Sámi Audiovisual Collection - Nilsson, Ragnhild (Critical Arts, 2024)
This article explores the representation of Sámi cultural heritage inaudiovisual archives, specifically focusing on the Sámi AudiovisualCollection research project and the work that has been done toestablish a Sámi film and television database, Sápmi on Film andTV (Sápmi på film och TV). It also provides insights into howIndigenous peoples‘ right to self-determination can beimplemented by working with archival material alongsideIndigenous institutions. The article highlights how historicalrepresentations of the Sámi have been shaped by outsiders’visions, often resulting in objectification and exoticization. Byworking with new metadata descriptions based on Sámilanguages and Sámi knowledge, a remediation of the old filmmaterial can be conducted and the archives can serve asimportant sources of Sámi cultural heritage. Emphasis is placedon the importance of making all material publicly accessible andthat it should be accompanied by contextual information andethical recommendations to address the racist expressions foundin some of the content. By making material concerningIndigenous peoples in the national archives available andsearchable, by creating new metadata in Indigenous languages,and by creating ethical recommendations regarding thecollection, new stories, new knowledge, and new history will beenabled to take shape for the future.